HIJRAH KE HABASIYAH: STRATEGI DAKWAH DAN DIPLOMASI RASULULLAH SAW DALAM MENGHADAPI PERSEKUSI QURAISY (KAJIAN HISTORIS TAHUN 615-616 M) - Masykur, Arif; Darmawan, Rizki; Zen, Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study historically and analytically examines the migration of early Muslims to Abyssinia (Ethiopia) during the 5th and 6th years of prophethood (615–616 AD). This event was not merely an escape from Quraysh persecution, but a carefully planned da'wa and diplomatic strategy initiated by the Prophet Muhammad SAW. Using historical method and a historical-descriptive-analytical approach grounded in classical sirah nabawiyah texts, contemporary academic scholarship, and recent peer-reviewed journal articles (2015–2024), this study finds: (1) the migration to Abyssinia was a strategic response to escalating Quraysh brutality; (2) Abyssinia was chosen based on King Negus Ashama ibn Abjar's reputation for justice; (3) Ja'far ibn Abi Talib's diplomacy at the Negus' court represents the first model of cross-cultural Islamic da'wa in history; (4) the success in gaining Negus' protection demonstrates Islam's universal message; and (5) this event laid the foundation for the spread of Islam in East Africa. The study also identifies the methodological relevance of this event for contemporary da'wa strategies amid global plurality. Prior research by Saufan (2015) and Siregar (2023) serves as a critical departure point expanded by this study.